Spread Indication of Underwater Surface Contaminants Using Magnetic Method (Case Study: TPA Supit Urang, Malang) - Arif Rahman Hakim; Adi Susilo; Sukir Maryanto (Natural B, Journal of Health and Environmental Sciences, 2014)
Research has been done on the spread of contaminants in the Supit Urang landfill, the city of Malang. The research was done in April 2013 - January 2014 in the area around Supit Urang landfill. The research purpose to determine the presence of contaminants in the Supit Urang landfill and distribution patterns. This research was begun by doing a data correction, consists of diurnal correction and IGRF correction so that got the total magnetic anomaly. Then, did reduction to the pole and upward continuation so that got the residual magnetic anomaly value ranging from -800 nT to 1100 nT. The results of data processing showed that contaminants in Supit Urang landfill accumulated on the inside of the landfill and then spreads in all directions with a depth of seepage reaches 25 meters. The spread of these contaminants are more inclined to the south because there is a river which is the discharge path of leachate from landfill to the river in the area. The results also showed the structure of the subsurface Supit Urang landfill dominated by sedimentary rocks such as sandstone, clay, tuff, tuff breccia and breccia. Based on the chemical test results, it showed contaminants in landfill is suspected to be leachate with susceptibility value between 0.0001 Wb/Am to 0.001 Wb/Am. Leachate from landfill contains some heavy metals with different concentrations, such as Cobalt (Co) 0.38 mg/L, Copper (Cu) 0.58 mg/L, Iron (Fe) 6.5 mg/L, Lead (Pb) 5.4 mg/L and Zinc (Zn) 4.8 mg/L.